Postnatal Exercise Partners Study (PEEPS): a pilot randomized trial of a dyadic physical activity intervention for postpartum mothers and a significant other. Issue 1 (1st January 2021) - Carr, Rachel Margaret; Quested, Eleanor; Stenling, Andreas; Thøgersen-Ntoumani, Cecilie; Prestwich, Andrew; Gucciardi, Daniel Frank; McVeigh, Joanne; Ntoumanis, Nikos
ABSTRACT: Background: Research suggests dyadic interventions can increase physical activity; such interventions are untested within postpartum parent couples. Methods: A three-armed pilot randomized trial addressed this gap and tested which type of dyadic intervention is most effective. Inactive postpartum mothers and a significant other were recruited in Australia ( n = 143 assessed for eligibility) and randomised in a single-blinded fashion (i.e. participants were blinded) to 1 of 3 dyadic conditions involving a single face-to-face session with access to web-based group support: a minimal treatment control ( n = 34), collaborative planning group ( n = 38), or collaborative planning + need supportive communication group ( n = 30). Participants were asked to wear their accelerometers for 8 days and completed self-report measures at baseline, end of intervention (week 4), and follow-up (week 12). We expected dyads in the collaborative planning + need supportive communication group would have the greatest increases in Physical Activity (PA), autonomous motivation, and partners' need supportive behaviours; and decreases in controlled motivation and controlling partner behaviours. Results: Results from 51 dyads using Bayesian actor-partner interdependence models provided some evidence for a small positive effect on total PA at follow-up for postpartum mothers in the collaborative planning group and for partners in the collaborative planning + need supportive communication group. Furthermore, partners in the collaborative planning + need supportive communication group were more likely to engage in some vigorous PA. At follow-up, postpartum mothers in the collaborative planning + need supportive communication group scored lower on personal autonomous reasons. Conclusions: The impact of prior specification mean intervention effects need to be interpreted with caution. Progression to a full trial is warranted.